Implementación de un plan de manejo de podas en el parterre de acceso a la Facultad de CAREN de las especies ornamentales acacia morada (acacia baileyana) y escobillón rojo (callistemon citrinus) del Campus Salache– 2022. - Tello Balseca, Erick Sebastián (2022)
The present research work was carried out in the Eloy Alfaro parish, located in the Latacunga canton, province of Cotopaxi, within the CAREN faculty facilities of the Technical University of Cotopaxi, keeping in mind the physiological and health situation of the individuals in study, it was proposed to carry out a monitoring to be able to implement a linear tree management plan in the access part to the CAREN faculty, the individuals under study present risks of contact with electrical wiring and avenues, for which the study was carried out. monitoring of the species obtaining the study variables such as: the evaluation of the sanitary state of the species where they focus on generating a diagnosis of the state of the crown to generate the activities, in addition to the dasometric characterization that allows identifying the species, the height of crown in addition to the total height, the individuals under study have acute angles generated by the various ramifications in a single area in addition to bifurcations, in order to establish pruning activities for its maintenance and structural improvement.